Arbeitsmärkte und Arbeitsbeziehungen in Osteuropa - Standing, Guy (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
This article provides an overview of recent changes in the former Soviet Union and other countries of Central and Eastern Europe. State regulation has been reduced through relaxation of statutory prescriptions and through privatization. Trade unions often retain significant nominal representative status, but have little effective regulatory power, and employers’ representation is fragmented. Although most countries have introduced tripartite institutions, real decision making takes place at company level where management is in the driving seat.